PEMANFAATAN BATANG PISANG DAN DAUN JATI SEBAGAI PAKAN TERNAK DAN KOMPOS MELALUI FERMENTASI - Hariyono Hariyono (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
During the dry season, farmers often find it difficult to obtain forage as a result of drought. As an alternative solution of these problems, made fodder from fermentation banana stems and teak leaves are drought-resistant which also produce compost that can be utilized as organic fertilizer. Preparation of animal feed and compost from banana and teak stems is done by demplot method in the field by involving community participation. The results of the manufacture of animal feed and compost can provide sustainable animal feed without season-influenced, and can provide organic fertilizer for farmers in the form of compost. From this activity it can be concluded that with the provision of animal feed and compost from drought-resistant local materials can reduce the cost of purchasing factory-made fodder and reduce the use of an organic fertilizer.